2012
DOI: 10.1111/j.1533-2500.2012.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Transversus Abdominis Plane Catheter for Chronic Abdominal Pain

Abstract: A successful TAP block confirmed the peripheral (somatic) source of the abdominal pain and provided temporary analgesia after which an indwelling catheter was inserted, which provided prolonged pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 12 publications
1
15
0
2
Order By: Relevance
“…Guirguis ve ark. geçirilmiş kolesistektomi cerrahisi ilişkili kronik karın duvarı ağrısı için 14 gün boyunca TAP blok kateteri ile sürekli infüzyon uyguladıkları olgunun 9 aylık takibin sonunda ağrı skorlarında anlamlı düşme ve yaşam kalitesinde artış olduğunu belirtmişlerdir (9).…”
Section: Discussionunclassified
“…Guirguis ve ark. geçirilmiş kolesistektomi cerrahisi ilişkili kronik karın duvarı ağrısı için 14 gün boyunca TAP blok kateteri ile sürekli infüzyon uyguladıkları olgunun 9 aylık takibin sonunda ağrı skorlarında anlamlı düşme ve yaşam kalitesinde artış olduğunu belirtmişlerdir (9).…”
Section: Discussionunclassified
“…Le territoire de ces deux nerfs, repérables en échographie, soit par visualisation directe [23], soit par la technique du TAP (transversus abdominis plane) block [24], peut être le siège de douleurs chroniques dans le cadre des séquelles de chirurgie herniaire [25].…”
Section: Névralgie Ilio-inguinale Et Ilio-hypogastriqueunclassified
“…Transversus abdominis plane (TAP)block, which is an analgesic technique used to treat both postoperative acute pain (16)(17)(18)(19)(20) and chronic pain (21), can be used in the surgical interventions involving the lower abdominal area. Previously performed with traditional methods (22)(23)(24), the TAP block has become more popular, together with the use of ultrasound (US).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers of the current study found many studies on chronic pain after inguinal hernia repair during an extensive search of the literature (26)(27)(28)(29); however, most of these studies were related to surgical techniques and equipment, and limited to the analgesic technique (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Therefore, the researchers conducted a retrospective study comparing the efficacy of intravenous (iv) analgesia after general anesthesia, TAP block after the induction of general anesthesia and before surgery and spinal analgesia on the development of chronic pain following inguinal hernia.…”
Section: Introductionmentioning
confidence: 99%